A Novel Amphibian Antimicrobial Peptide, Phylloseptin-PV1, Exhibits Effective Anti-staphylococcal Activity Without Inducing Either Hepatic or Renal Toxicity in Mice - Liu, Yue; Shi, Daning; Wang, Jin; Chen, Xiaoling; Zhou, Mei; Xi, Xinping; Cheng, Jianming; Ma, Chengbang; Chen, Tianbao; Shaw, Chris; Wang, Lei (Frontiers in Microbiology, 2020)
In order to part address the problem of drug-resistant pathogens, antimicrobial peptides (AMPs) have been proposed as alternatives to traditional antibiotics. Herein, a novel phylloseptin peptide, named phylloseptin-PV1 (PPV1), is described from the defensive skin secretion of the Neotropical white-lined leaf frog, Phyllomedusa vaillantii. The peptide was synthesised by solid phase peptide synthesis (SPPS) and purified by RP-HPLC, prior to assessment of its biological activities. PPV1 not only demonstrated potent antimicrobial activity against planktonic ESKAPE microorganisms and the yeast, Candida albicans, but also inhibited and eradicated Staphylococcal aureus and MRSA biofilms. The antimicrobial mechanism was shown to include permeabilisation of target cell membranes. The in vivo antimicrobial activity of the peptide was then evaluated using mice. PPV1 also exhibited antiproliferative activity against the cancer cell lines, H157, MCF-7, and U251MG, but had a lower potency against the normal cell line, HMEC-1. Although, the peptide possessed a moderate haemolytic action on mammalian red blood cells in vitro, it did not induce significant hepatic or renal toxicity in injected infected mice. These studies have thus found PPV1 to be a potent phylloseptin group AMP, which can effectively inhibit staphylococci, both in vitro and in vivo, without eliciting toxicity. These data thus provide support for further evaluation of PPV1 as a novel antimicrobial agent with therapeutic potential.